Numerical Simulation of Hydrogen Leakage and Diffusion Process of Fuel Cell Vehicle - Mingyu Jiao; Haoran Zhu; Jinglong Huang; Xin Zhang (World Electric Vehicle Journal, 2021)
Regarding the problem of hydrogen diffusion of the fuel cell vehicle (HFCV) when its hydrogen supply system leaks, this research uses the FLUENT software to simulate numerical values in the process of hydrogen leakage diffusion in both open space and closed space. This paper analyzed the distribution range and concentration distribution characteristics of hydrogen in these two different spaces. Besides, this paper also took a survey about the effects of leakage rate, wind speed, wind direction in open space and the role the air vents play on hydrogen safety in closed space, which provides a reference for the hydrogen safety of HFCV. In conclusion, the experiment result showed that: In open space, hydrogen leakage rate has a great influence on its diffusion. When the leakage rate doubles, the hydrogen leakage range will expand about 1.5 times simultaneously. The hydrogen diffusion range is the smallest when the wind blows at 90 degrees, which is more conducive to hydrogen diffusion. However, when the wind direction is against the direction of the leakage of hydrogen, the range of hydrogen distribution is maximal. Under this condition, the risk of hydrogen leakage is highest. In an enclosed space, when the vent is set closest to the leakage position, the volume fraction of hydrogen at each time is smaller than that at other positions, so it is more beneficial to safety.